The interplay of evidence and knowledge for social work practice in a health setting - Fielding, Angela; Crawford, Frances; Leitmann, Sabina; Anderson, Judi (Mark Allen Publishing Ltd., 2009)
Aims: There is a growing body of research and scholarly literature addressing, from a range of philosophical views, the nature and effectiveness of evidence-based practice across health and human services. Influenced by developments in the USA and UK, there is an increasing requirement in Australia for evidence-based accountability from professional practitioners. Following Clifford Geertz’s dictum that to understand a practice it is necessary to study what it is that practitioners do, this interpretive study explores how experienced and reputedly effective social workers use knowledge in practice. Methods: The study was conducted in 2007/08 at a West Australian tertiary hospital. A purposive sample of four social workers, identified by their manager as experienced and effective practitioners, were interviewed on their practice in a case study of their choice. Interview data were transcribed and analysed thematically alongside official case notes to explore the ways in which evidence and knowledge interplay in shaping effective practice and the ways this is recorded for agency purposes. Findings: Practitioner thick descriptions on two cases revealed mediation and interaction with both empirical and reflective types of knowledge, with a dynamic interplay of evidence, knowledge and knowledge making, and practice wisdom. Conclusions: The authors argue that social workers are active agents who use and generate knowledge while they are making practice decisions based on their assessment of empirical knowledge, values, principles, and tacit knowledge. In this research project, researchers and practitioners examined and articulated effective social work practice to illustrate the ways in which multiple forms of knowledge are incorporated.